3D Co‐Printing of 3D Electronics with a Dual Light Source Technology. Issue 9 (23rd June 2021) - Xiao, Junfeng; Zhang, Dongxing; Guo, Qiuquan; Yang, Jun
Abstract: This study reports a new strategy—3D co‐printing technology by collaboratively employing a dual‐light curing process—to fabricate 3D electronics selectively either deposited on a free‐form surface or embedded within a bulk structure. The 3D co‐printing technology only involves one printing material, which works for both the construction of polymeric structures and the metallization process of conductive circuits resulted from the metal precursor loaded in photosensitive resin. The photoreduction of metal nanoparticles (NPs) can be efficiently activated with a second laser scanning. 3D co‐printing technology addresses the challenge of conventional methods requiring multiple materials deposition processes. The resultant conductive trace composed of NPs exhibits a superior resistivity as low as ≈6.12 µΩ m. The resistivity is further controllable ranging from 10 −6 to 10 Ω m through adjusting the material formulation and processing parameters. This study has demonstrated that the proposed 3D co‐printing is a high‐efficiency and low‐cost co‐printing approach which opens a new avenue of making 3D electronics. Abstract : This work presents a new strategy – 3D co‐printing technology to fabricate 3D electronics by collaboratively employing a dual‐light curing process. Here, integrating the metal precursor into the 3D printing material enables the construction of polymeric structures and printing of conductive traces simultaneously, addressing the challenges of 3D electronics fabrication brought by the traditional multimatrial deposition.